2021
DOI: 10.47144/phj.v53i4.2001
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Cardiogenic Shock in Patients Presenting With Nstemi and Younger Than 45 Years of Age

Abstract: Objective: The objective of this study was to assess the frequency of cardiogenic shock in patients of younger than 45 years of age presenting with NSTEMI. Methodology: A hospital based Cross sectional study has been conducted in a tertiary hospital of Isra University Hospital, Hyderabad in the Department of Cardiology. This study was started in September 2017 and completed on March 2019 and recruited a total of 321 patients NSTEMI patients having age less than 45 years of either gender to determine the burden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The AssociATion beTween ViTAmin D Deficiency AnD RecuRRenT TonsillophARyngiTis between low levels of 25-hydroxyvitamin D and the susceptibility to upper respiratory tract infections (URTIs) (8,34,56). Studies have established connections between vitamin D levels and conditions such as adenotonsillar hypertrophy, TPS, PFAPA syndrome and otitis media with effusion (33,(57)(58)(59). It has also been observed that the general incidence of URTIs inversely correlates with vitamin D deficiency (22).…”
Section: Discussionmentioning
confidence: 99%
“…The AssociATion beTween ViTAmin D Deficiency AnD RecuRRenT TonsillophARyngiTis between low levels of 25-hydroxyvitamin D and the susceptibility to upper respiratory tract infections (URTIs) (8,34,56). Studies have established connections between vitamin D levels and conditions such as adenotonsillar hypertrophy, TPS, PFAPA syndrome and otitis media with effusion (33,(57)(58)(59). It has also been observed that the general incidence of URTIs inversely correlates with vitamin D deficiency (22).…”
Section: Discussionmentioning
confidence: 99%
“…15 Studies have shown the association between vitamin D levels and recurrent tonsillitis, adenotonsillar hypertrophy, tonsillopharyngitis, otitis media with effusion. 15,21,22 Factors which influences the vitamin D levels in children are maternal factors, environmental factors, dietary factors, exposure to sunlight, regional clothing habits. 22,23 In present study the mean serum vitamin D levels of group 1-3 were 54.22±16.33 nmol/l, 49.17±15.11 nmol/l and 91.23±14.31nmol/l respectively.…”
Section: Discussionmentioning
confidence: 99%